Quality of work and job satisfaction: comparing female part-time work in four European countries. Issue 3 (1st September 2016) - Gallie, Duncan; Gebel, Michael; Giesecke, Johannes; Halldén, Karin; Van der Meer, Peter; Wielers, Rudi
ABSTRACT: Adding to the debate on the integrative or marginalizing nature of female part-time work, this article provides a comparative analysis of the implications of female part-time work for different intrinsic job quality dimensions and job satisfaction. Drawing on national micro-data from Britain, Germany, the Netherlands, and Sweden, our multivariate analyses show cross-national similarities in terms of lower job learning opportunities for female part-timers. We found a significantly higher incidence of repetitiveness only among Swedish female part-timers and lower degrees of task discretion among British, Dutch, and Swedish women working part-time hours. Female part-timers were either equally satisfied with their work as female full-timers or even more satisfied. This held true also after accounting for the lower intrinsic job quality of part-time work. While women working part-time hours were as affected by their job quality characteristics as were full-timers, we conclude that the shorter hours of work per se provide an important additional source of job satisfaction.